Idealized Study of a Static Electrical Field on Charged Saltating Snow Particles - Yu, Hongxiang; Li, Guang; Huang, Ning; Lehning, Michael (Frontiers in Earth Science, 2022)
Strong electric fields, with the values of tens kV/m near the surface, are observed during drifting and blowing snow events. Charge separation can significantly affect particle motion. Although several investigations attempted to shed light on the mechanisms of charge separation and the resulting electric field structure, few studies pay attention to the effect of electrification on the particle trajectory, which may influence the transport mechanism. In this work, we studied trajectories of individual, charged particles in an idealized static electrical field by solving the equations of motion in a neutral atmospheric boundary layer. The results show that negatively charged particles have a lower saltation height while positively charged particles jump higher as long as friction velocities are small. This effect reverses for higher friction velocities as rebound velocities start to dominate over vertical acceleration. We find regimes, in which charge separation leads to suspension of particles close to the ground. The threshold condition for this saltation-suspension transition is related to the rebound velocity and charge-to-mass ratio of the charged particle. Our study is a first step towards a better understanding on the influence of charge separation on drifting snow and should lead to include this effect in state of the art saltation models.